A Concise Review of Current Radiopharmaceuticals in Tumor Angiogenesis Imaging - Lu, Xia; Fu Wang, Rong (Current Pharmaceutical Design, 2012)
Angiogenesis is necessary for tumor growth, without which a tumor can not grow beyond a few millimeters in diameter. This review summarizes the current status on the research of peptide Arg-Gly-Asp (RGD) and Arg-Arg-Leu (RRL) as well as its derivatives applied in tumor angiogenesis imaging and targeted therapy with single photon emission tomography (SPECT) and positron emissiontomography (PET). Peptide RGD sequence Arg-Gly-Asp targeted and combined to integrin αvβ3 which has been overexpressed on tumor endothelial cells and many different tumor cellsis a robust site for tumor angiogenesis molecular imaging and targeted therapy. The vari-ous derivatives of RGD were focused on optimizing its biological characteristics including affinity, targeting efficacy and pharmacoki-netics. The other alternative novel tumor angiogenesis molecular imaging agent is RRL peptide which targeted to tumor derived endothe-lial cells and then applied to visualize tumor angiogenesis with enhanced ultrasonic imaging, optical imaging and SPECT in animal. These novel peptide agents can have promising applications for tumor angiogenesis imaging and antiangiogenic tumor therapy.
Keywords: Tumor molecular imaging